Stock Illiquidity, option prices, and option returns - Stefan Kanne; Olaf Korn; Marliese Uhrig-Homburg (University of Cologne, Centre for Financial Research (CFR), 2016)
We provide evidence of a strong effect of the underlying stock's illiquidity on option prices by showing that the average absolute difference between historical and implied volatility increases with stock illiquidity. This pattern translates into significant excess returns of option trading strategies that are not explained by common risk factors. Simulation results show, however, that our results can be explained by the hedging costs of market makers who are net long in options on some underlyings and net short in options on other underlyings. Our empirical findings are robust with respect to the chosen illiquidity measure, the measure of option expensiveness, and the return period.
Keywords: G12; G13; 330; illiquidity; equity options; option returns; option strategies